Penentuan Nilai Surface Loading Rate (Vo) Dengan Menggunakan - Hamdani Hamdani; Lita Darmayanti; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
In general, in the water treatment process, the process of separating water from solids occurs in the form of flocculant particles or sedimentation type II. Before planning to process river water into clean water, it is necessary to analyze the rate of deposition as the basis for the design criteria that will be used in the planning of the sedimentation basin. The sampling points are at a depth of 10, 30, 50, 70 and 90 cm and the sampling time ranges are 10, 20, 30, 45 and 60 minutes. The results obtained in order to achieve an efficiency of 70% in sedimentation processing, an overflow rate (Vo) of 1.3 m / h is required. Keywords: column settling, sedimentation type II, surface loading, papaya seeds